Influence of particulate matter during seasonal smog on quality of life and lung function in patients with chronic obstructive pulmonary disease - Chaicharn Pothirat (2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. The impact of outdoor air pollution on the quality of life (QoL) of chronic obstructive pulmonary disease (COPD) patients, as measured by the COPD assessment test (CAT) questionnaire, is limited. The aim of this study was to determine the impact of a short-term increase in outdoor particulate matter in which the particles are less than 10 microns in diameter (PM10) during a seasonal smog period on QoL, symptoms, and lung function in COPD patients. This prospective observational study was conducted at Chiang Dao Hospital, Chiang Mai, Thailand between March and August 2016. Measurement of QoL, severity of dyspnea, forced vital capacity (FVC), and forced expiratory volume in the first second (FEV1) were performed at both high and low PM10 periods. Fifty-nine patients met the inclusion criteria for enrollment into the study, with the mean age being 71.5 ± 8.0 years. Total CAT score, but not mMRC score, was statistically higher during the high PM10 period. The two lung function parameters, FVC and FEV1, were significantly lower at the high PM10 compared to the low PM10 period. We concluded that exposure to PM10 during the seasonal smog period resulted in short-term negative impact on the quality of life and lung function in COPD patients.